Determinants of exchange rate volatility in Asian countries - Chai, Jing Thung; Eng, Kah Mun; Kong, Seen Yee; Wong, Hui Ling; Yong, Chee Fung (2020)
The intention of this research is to determine the relationship between the exchange rate volatility and the independent variables which includes unemployment rate, consumer price index, foreign direct investment, interest rate and terms of trade in Asian countries. Secondary data is the sourced data used within the period of year 2007 to 2016 which data obtained from the World Bank Data sources. On the other hand, the techniques that implemented to estimate the model was the Ordinary Least Square (OLS). The result shows that the exchange rate volatility was being influenced by the unemployment rate, consumer price index, foreign direct investment, interest rate and terms of trade. However, the results show it has a direct and statistically significant relationship but there is an insignificant relationship and mix result between the exchange rate volatility and the independents variables. In addition, a diagnostic checking is conducted by using the E-view 11 software to run out the collected data within 10 years in 5 different Asian countries. According to the literature review, the researcher studies shows different results which includes positively and significant relationship, negatively and insignificant relationship as well as mix result between the exchange rate volatility and independent variables. Although this research experienced and occurred some limitation, hence the recommendation has been suggested to enhance for the future researchers.